An Update on Drugs Used for Lumbosacral Epidural Anesthesia and Analgesia in Dogs - Steagall, Paulo V. M.; Simon, Bradley T.; Teixeira Neto, Francisco J.; Luna, Stelio P. L. (Frontiers in Veterinary Science, 2017)
This review aims to report an update on drugs administered into the epidural space for anesthesia and analgesia in dogs, describing their potential advantages and disadvantages in the clinical setting. Databases searched include Pubmed, Google scholar, and CAB abstracts. Benefits of administering local anesthetics, opioids and alpha2- agonists into the epidural space include the use of lower doses of general anesthetics (anesthetic ‘sparing’ effect), perioperative analgesia, and reduced side effects associated with systemic administration of drugs. However, the potential for cardiorespiratory compromise, neurotoxicity, and other adverse effects should be considered when using the epidural route of administration. When these variables are considered, the epidural technique is useful as a complementary method of anesthesia for preventive and postoperative analgesia and/or as part of a balanced anesthesia technique.